The Effect of Text Message Reminders on Patient Compliance with Functional Appliance Therapy as Measured by Theramon Sensors - Higgins, Emily (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2021)
Aims: The aim of this study was to evaluate whether text message reminders have an effect on patient compliance with twin block appliances. A secondary aim was to determine whether text message reminders influenced the number of days where over 18 hours or 8 hours of wear was recorded. Orthodontic patients who present with class II skeletal discrepancies are often treated with a functional appliance to correct their anteroposterior relationship before proceeding to fixed appliances. Although reminders have been associated with increased compliance in the dental and orthodontic setting, this is the first study to examine the effect of text message reminders with the twin block appliance. Materials and Methods: A consecutive sample of 59 patients between 11-15 years of age and with a 5a Index of Orthodontic Treatment Need (IOTN) were recruited. These patients were randomly allocated into the control group (CG) and study group (SG). Both groups received a standardised twin block design with a thermosensitive sensor (Theramon?) embedded in the maxillary block. Both groups were asked to wear their appliances full time, excluding during eating, cleaning and contact sports. The CG received verbal instruction as well as a leaflet instructing them on how to wear and care for their appliances. In addition to the same verbal and written instruction received by the CG, the SG received text message reminders to wear their appliances every 3 days. At each visit, data on wear-time was uploaded from the Theramon? sensors onto cloud software. Patients in both groups were asked to fill out wear diaries and submit these at each visit. The follow-up period was 4 months in duration. Results: The median hours/day of wear recorded was 13.77 (IQR 10.19) in the CG and 17.72 (IQR 5.62) in the SG. There was no statistically significant difference between the CG and SG for wear times reported by the Theramon? sensors (p=.16). There was no statistically significant difference in the number of days where over 18 hours or 8 hours of wear was recorded. Insufficient completed wear diaries were returned and therefore it was not possible to carry out a formal analysis on the data. Conclusions: The study concluded that text message reminders have no statistically significant influence on patient compliance with twin block appliances. In addition, text message reminders have no statistically significant influence on the number of days where over 18 hours or 8 hours of wear is recorded. Wear diaries are not a useful mechanism for measurement of subjective wear times and consideration should be given to the use of intraoral sensors to more reliably measure compliance.
APPROVED
Keywords: twin block; reminders; compliance